Concurrent validity of a continuous glucose-monitoring system at rest and during and following a high-intensity interval training session - Clavel, P.; Tiollier, E.; Leduc, C.; Fabre, M.; Lacome, M.; Buchheit, M. (International Journal of Sports Physiology and Performance, 2022)
Purpose: To assess the concurrent validity of a continuous blood-glucose-monitoring system (CGM) postbreakfast, preexercise, exercise, and postexercise, while assessing the impact of 2 different breakfasts on the observed level of validity.